Seven new Tettigoniidae (Orthoptera) and a new Blattellidae (Blattodea) from the Durmitor area of Montenegro with notes on previously known taxa - Ingrisch, Sigfrid; Pavićević, Dragan (Zootaxa, 2010)
Eight new species or subspecies of orthopteroid insects discovered by the authors during expeditions to the Durmitor area in Montenegro are described; seven of them belong to Ensifera, Phaneropteridae: Leptophyes intermedia sp. n., Isophya clara sp. n., Poecilimon pseudornatus sp. n., Poecilimon nonveilleri sp. n., Poecilimon affinis dinaricus ssp. n., Poecilimon albolineatus sp. n., Tettigoniinae: Pachytrachis tumidus sp. n., and one to Blattodea, Ectobiinae: Phyllodromica montenegrina sp. n. Diagnostic keys to taxa of the P. affinis-ornatus group and to the species of Pachytrachis are provided. Poecilimon elegans Brunner v.W., 1878 is re-described and a lectotype selected. Diagnostic notes and images for species related to the new taxa are also given. Within the genera Isophya, Poecilimon and Pachytrachis stridulation is used to verify the status of the species studied.